ISLAMIC GUIDANCE AND COUNSELING SERVICES AT MADRASAH IN INTERVENTING CASES OF VIOLENCE AGAINST CHILDREN IN CENTRAL LOMBOK DISTRICT - Wahid, Lalu Abdurrachman (Universitas Islam Negeri Mataram, 2025)
The purpose of this study is first to describe the general picture of the forms of cases of Violence Against Children (KTA), identify and analyse the steps for handling cases of Violence Against Children (KTA), describe and outline efforts to prevent cases of Violence Against Children (KTA) through Islamic Guidance and Counseling services at Madrasahs. The research method uses qualitative research with a descriptive analysis type. Data sources are obtained from interviews, observations, and documentation. Data analysis techniques include data reduction, data presentation, deductive and inductive qualitative analysis and drawing conclusions or verification. The results of the study show a general picture of the forms of cases of Violence Against Children (KTA), such as physical, psychological, economic, social, verbal, and cyber violence, and no indication of sexual violence was found. Steps for handling cases ofViolence Against Children (KTA) carried out by BK teachers include early identification and detection, case assessment, intervention planning, intervention implementation, empowerment of parents and teachers, monitoring and evaluation, and follow-up. Efforts to prevent cases of violence against children (KTA) through education and socialisation, development of child-friendly school programs, formation of violence prevention teams, monitoring and early detection, strengthening guidance and counselling services, and strengthening the role of parents.